2-(fluorine-18)-fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography after breast conserving surgery: Correlation with molecular markers of breast cancer - TUROĞLU, HALİL TURGUT; GÜLLÜOĞLU, MAHMUT BAHADIR; UĞURLU, MUSTAFA ÜMİT; İNANIR, SABAHAT; ÖZGÜVEN, SALİH; ERDİL, TANJU YUSUF (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2016)
Aim: To investigate the role of 2-(fluorine-18)-fluoro-2-deoxy-D-glucose (F-18-FDG) positron emission tomography/computed tomography (PET/CT) early after breast-conserving surgery (BCS) in patients with breast cancer (BC) and whether we can determine which molecular biomarkers of breast carcinoma put the patients at risk. Materials and Methods: This retrospective study involved 88 patients with histologically proven T1 or T2 BC, who were treated with BCS and underwent F-18-FDG PET/CT study. The correlation between biological markers (estrogen receptor, progesterone receptor, human epidermal growth factor receptor 2 [HER2], and Ki-67) of the primary tumor and F-18-FDG PET/CT findings was analyzed. Results: F-18-FDG PET/CT demonstrated the presence of BC disease (locoregional disease [LRD], distant metastases, or contralateral BC) in 26 of 88 patients (29.5%). Regarding immunohistochemical profiles, BC expressing high levels of Ki-67 were associated with an increased percentage of LRD, which was the major recurrence pattern on F-18-FDG PET/CT. Although the BC disease was observed more commonly in patients with HER2 positivity compared to those of HER2 negative, the difference did not reach statistical significance. The patients with T2 tumor or a higher histopathological grade had a higher percentage of BC disease. Conclusions: This study demonstrated that patients with early stage BC treated with BCS have a remarkable risk of the presence of BC even early after surgery, and there was a clinically important relationship between F-18-FDG PET/CT findings and biological markers of BC. These findings suggest that high-risk molecular biomarkers (Ki-67, HER2) can be taken into account in the decision-making the process for both preoperative imaging and planning of the surgical approach.
Keywords: Breast neoplasms; fluorodeoxyglucose F18; human epidermal growth factor receptor 2; Ki-67 antigen; mastectomy; positron emission tomography; segmental; F-18-FDG PET/CT; SUBTYPES; THERAPY; FDG; MASTECTOMY; RECEPTOR; IMPACT